Improving the Equity-Efficiency Trade-off: Mandatory Savings Accounts for Social Insurance - Lans Bovenberg; Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2003)
In the modern welfare state a substantial part of an individual's tax bill is transferred back to the same individual taxpayer in the form of social transfers. This provides a rationale for financing part of social insurance through mandatory savings accounts. We analyze the behavioral and welfare effects of compulsory savings accounts in an intertemporal model with uncertainty, endogenous involuntary unemployment and retirement decisions, credit constraints, and heterogeneous agents. We show that the introduction of (early) retirement and unemployment accounts generates a Pareto improvement by enabling the government to provide lifetime income insurance and liquidity insurance in a more efficient manner.
Keywords: 330